The effect of local original revenue (PAD), special allocation fund (DAK) and general allocation fund (DAU) on capital expenditure in Bengkulu Province - Fadli; Mayasari, Citra (Journal of Economic, Business & Accounting Research, 2024)
Background: The implementation of regional autonomy will directly affect the regional financial financing, management and supervision system. The regional financing system in the context of regional autonomy is one of the most important aspects. To realize this, regional governments have rights and obligations over regional finances in organizing their regional government. Therefore, the regional government creates a Regional Revenue and Expenditure Budget/Anggaran Pendapatan dan Belanja Daerah (APBD) as an annual regional financial plan that is determined through Regional Regulations. APBD contains regional government revenues and expenditures in a certain period. This research aims to prove whether there is an influence of Regional Original Income, General Allocation Funds, and Special Allocation Funds on capital expenditure of district/city governments in Bengkulu Province. Method: This research uses samples from the financial reports of district/city governments throughout Bengkulu Province which have been audited by the Republic of Indonesia Financial Audit Agency/Badan Pemeriksa Keuangan Republik Indonesia (BPK) from 2019-2022. Finding: Theoretically, it is hoped that this research will be useful as material for building new concepts and can be useful as a reference for further research. A limitation in this research is the availability of data or reports needed to carry out this research. So, researchers look for data or reports on other websites which takes quite a long time. Conclusion: The results of this study indicate that the Regional Original Income and Special Allocation Fund variables have no effect on capital expenditure, and the General Allocation Fund variable has an effect on capital expenditure. Novelty/Originality of this study: This study presents a comprehensive analysis of the influence of Local Revenue, General Allocation Fund, and Special Allocation Fund on capital expenditure in districts/cities in Bengkulu Province from 2019-2022. The results of this study provide new insights into the dynamics of regional finance in the context of regional autonomy in Bengkulu Province, which can be used as a reference for optimizing regional budgets in the future.